Risk factors for transient dysfunction of gas exchange after cardiac surgery - Cristiane Delgado Alves Rodrigues; Marcos Mello Moreira; Núbia Maria Freire Vieira Lima; Luciana Castilho de Figueirêdo; Antônio Luis Eiras Falcão; Orlando Petrucci Junior; Desanka Dragosavac (Brazilian Journal of Cardiovascular Surgery, 2015)
Objective: A retrospective cohort study was preformed aiming to verify the presence of transient dysfunction of gas exchange in the postoperative period of cardiac surgery and determine if this disorder is linked to cardiorespiratory events. Methods: We included 942 consecutive patients undergoing cardiac surgery and cardiac procedures who were referred to the Intensive Care Unit between June 2007 and November 2011. Results: Fifteen patients had acute respiratory distress syndrome (2%), 199 (27.75%) had mild transient dysfunction of gas exchange, 402 (56.1%) had moderate transient dysfunction of gas exchange, and 39 (5.4%) had severe transient dysfunction of gas exchange. Hypertension and cardiogenic shock were associated with the emergence of moderate transient dysfunction of gas exchange postoperatively (P=0.02 and P=0.019, respectively) and were risk factors for this dysfunction (P=0.0023 and P=0.0017, respectively). Diabetes mellitus was also a risk factor for transient dysfunction of gas exchange (P=0.03). Pneumonia was present in 8.9% of cases and correlated with the presence of moderate transient dysfunction of gas exchange (P=0.001). Severe transient dysfunction of gas exchange was associated with patients who had renal replacement therapy (P=0.0005), hemotherapy (P=0.0001), enteral nutrition (P=0.0012), or cardiac arrhythmia (P=0.0451). Conclusion: Preoperative hypertension and cardiogenic shock were associated with the occurrence of postoperative transient dysfunction of gas exchange. The preoperative risk factors included hypertension, cardiogenic shock, and diabetes. Postoperatively, pneumonia, ventilator-associated pneumonia, renal replacement therapy, hemotherapy, and cardiac arrhythmia were associated with the appearance of some degree of transient dysfunction of gas exchange, which was a risk factor for reintubation, pneumonia, ventilator-associated pneumonia, and renal replacement therapy in the postoperative period of cardiac surgery and cardiac procedures.